2018
DOI: 10.1007/s00259-018-4161-6
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of [11C]PBR28 in Parkinson’s disease patients does not indicate increased binding to TSPO despite reduced dopamine transporter binding

Abstract: PurposeTo examine the hypothesis that cerebral binding to the 18 kDa translocator protein (TSPO), a marker of microglia activation, is elevated in Parkinson’s disease (PD), and to assess the relationship between brain TSPO binding and dopaminergic pathology in PD.MethodsThe radioligand [11C]PBR28 was used for quantitative assessment of brain TSPO in 16 control subjects and 16 PD patients. To analyse the relationship between dopaminergic pathology and brain TSPO binding, PET studies of the dopamine transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 46 publications
10
50
0
Order By: Relevance
“…Basically, identical observations were made by Varnas et al, who conducted similar research using 11C-PBR28 [63]. However, this study also noted that the significantly lower affinity of this ligand for LAB than 11C-PK11195, could be the reason for the decreased PET signal of 11C-PBR28 in PD patients [63]. Furthermore, it is known that second-generation TSPO tracers show additional limitations, such as a low quality of the images obtained for LABs, which limits their clinical value.…”
Section: Tspo and Parkinson Disease (Pd)supporting
confidence: 60%
See 1 more Smart Citation
“…Basically, identical observations were made by Varnas et al, who conducted similar research using 11C-PBR28 [63]. However, this study also noted that the significantly lower affinity of this ligand for LAB than 11C-PK11195, could be the reason for the decreased PET signal of 11C-PBR28 in PD patients [63]. Furthermore, it is known that second-generation TSPO tracers show additional limitations, such as a low quality of the images obtained for LABs, which limits their clinical value.…”
Section: Tspo and Parkinson Disease (Pd)supporting
confidence: 60%
“…However, within these three groups in the brain regions of interest, no significant alterations were discovered in the volume of distribution (VT) between healthy persons and PD patients, suggesting that genetic variations concerning TSPO binding affinity have little effect on PD risk [62]. Basically, identical observations were made by Varnas et al, who conducted similar research using 11C-PBR28 [63]. However, this study also noted that the significantly lower affinity of this ligand for LAB than 11C-PK11195, could be the reason for the decreased PET signal of 11C-PBR28 in PD patients [63].…”
Section: Tspo and Parkinson Disease (Pd)mentioning
confidence: 53%
“…Several PET studies with radioligands for 18-kDa translocator protein (TSPO), which is highly expressed in activated microglia in the brain [ 112 ], such as 11 C-( R )-PK11195 and 11 C-DPA713, revealed increased cortical uptake in patients with Parkinson’s disease, especially in the early stage of the disease [ 113 , 114 , 115 ]. While recent PET studies with other TSPO radioligands, 11 C-PBR28 and 18 F-FEPPA, showed conflicting results [ 116 , 117 ], the PET studies that yielded positive results indicated that neuroinflammation due to microglia activation occurs in the early phase of neurodegeneration in Parkinson’s disease [ 113 , 114 , 115 ]. These findings of neuroinflammation in the early stage contrast with the 62 Cu-ATSM PET studies showing that oxidative stress increases with disease progression [ 11 , 13 , 103 ].…”
Section: Oxidative Stress Imaging In Parkinson’s Diseasementioning
confidence: 99%
“…Initial studies with the first-generation TSPO radioligand [ 11 C]PK11195 have reported increased binding to TSPO in PD, as well as in MSA, PSP, and CBD. Subsequent studies in PD patients with second-generation TSPO radioligands have not replicated the initial findings [46,47]. Therefore, it is still controversial whether it is possible to image microglia activation in PD, considering the complexity of the process and the different expression in relation to the stage of the disease.…”
Section: Molecular Imaging In Parkinson's Disease-dr Andrea Varronementioning
confidence: 99%